Designing A Web-Based Employee Payment Information System For The Nutritional Culture And Tourism Office - M irsyan antony manday, Irsyanmanday; Amanda Putri, Raissa (Ali Institute or Research and Publication, 2023)
Employees were previously paid directly by people and. Now. Employee payments are made instantly. The world of labor is also affected by technology advancements, which can move quite quickly.Time makes it possible for humans to do their work quickly in general. Today, a lot of businesses use technology to expedite work. Payroll information system that can help with data processing payroll for better management of payroll computations, pay stubs, and necessary reports. Based on these issues, research was done to learn the specifications needed to create an employee payroll information system for the plan. This design's outcome isemployee payroll was digitized using a web-based information system. This system was created to facilitate and minimize the company's performance in processing payroll data. processes used to calculate employee salaries. The Culture Department continues to prepare payroll reports manually, and there are still numerous challenges involved. So, in order to construct a based application, this is required. The website makes use of MySQL to make employees' job more productive. Additionally, this method enforces absenteeism for workers, and if they are ill while on leave or without notice, their pay will be withheld in accordance with the guidelines of the North Sumatra culture and tourism agency.